A Longitudinal Study of Serum Lipoproteins in Relation to Endogenous Reproductive Hormones during the Menstrual Cycle: Findings from the BioCycle Study - Mumford, Sunni L. (The Endocrine Society, 2010)
Context: Exogenous estrogens have been shown to affect the lipid profile, leading to the hypothesis that endogenous estrogens may have similar effects. Objective: The objective of the study was to evaluate the association between endogenous estrogen and serum lipoproteins across the menstrual cycle. Design: This was a prospective cohort study. Setting: The study was conducted at the University at Buffalo, 2005–2007. Participants: Participants included 259 healthy, regularly menstruating women aged 18–44 yr. Main Outcome Measures: Serum levels of total, high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterol, and triglycerides measured up to eight times per cycle for up to two cycles were measured. Results: Total and LDL cholesterol were lower during the luteal phase as compared with the follicular phase (P < 0.001), and HDL levels were highest around ovulation (P < 0.001). More women were classified above the desirable range (LDL ≥130 mg/dl or total cholesterol ≥200 mg/dl) when measured during the follicular phase. Estradiol was positively associated with HDL in acute effects models [beta = 0.019, 95% confidence interval (CI) 0.015, 0.022] and inversely associated with total (beta = −0.017, 95% CI −0.020, −0.014) and LDL cholesterol (beta = −0.023, 95% CI −0.027, −0.018) and triglycerides (beta = −0.041, 95% CI −0.054, −0.029) in persistent effects models. Conclusions: Endogenous estrogen, like exogenous estrogen, appears to have beneficial effects on the lipid profile. Because lipoprotein cholesterol levels vary across the menstrual cycle, cyclic variations in lipoprotein levels may need to be considered in the design and interpretation of studies in reproductive-age women and in the clinical management of women’s cholesterol.